2020
DOI: 10.4067/s0718-09342020000100319
|View full text |Cite
|
Sign up to set email alerts
|

La habilidad léxico-semántica en la Enfermedad de Alzheimer: Un estudio de la fluidez verbal con categorías semánticas

Abstract: Language impairments in Alzheimer's disease (AD) primarily affect lexical and semantic levels, which significantly depend on the speaker's memory state. Qualitative shifts in semantic memory are due to neurodegenerative processes underlying dementia and give rise to anomia, or the speaker's inability to access and retrieve lexical units and their conceptual backgrounds. In this paper we aim at studying cognitive and semantic features of anomic deficit in AD and exploring the possibility to apply them in tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
4
Order By: Relevance
“…Los datos demuestran que el GC logra puntajes más altos y con desempeño típico en relación con el GDTA, que presenta resultados que posicionan los sujetos como con deterioro cognitivo (26)(27)(28) . Cabe señalar que en relación con niveles de funcionalidad entregados pela escala de Pfeffer, el puntaje de cuatro de los participantes residentes en ELEAMs se presente más descendido probablemente porque por norma general no pueden cumplir con actividades diarias como cocinar y bañarse, por ejemplo, porque deben ser siempre asistidos independientemente de su nivel cognitivo o funcional.…”
Section: Resultsunclassified
“…Los datos demuestran que el GC logra puntajes más altos y con desempeño típico en relación con el GDTA, que presenta resultados que posicionan los sujetos como con deterioro cognitivo (26)(27)(28) . Cabe señalar que en relación con niveles de funcionalidad entregados pela escala de Pfeffer, el puntaje de cuatro de los participantes residentes en ELEAMs se presente más descendido probablemente porque por norma general no pueden cumplir con actividades diarias como cocinar y bañarse, por ejemplo, porque deben ser siempre asistidos independientemente de su nivel cognitivo o funcional.…”
Section: Resultsunclassified
“…A comparative analysis of semantic fluency task in 15 languages (Ardila 2020) showed that such a highly universal semantic category as 'animals' can report significant differences in the number of elicited words when all other relevant variables are controlled for. Surprisingly, a recent experimental research (Ivanova et al 2020) also proved that 'animals' is not sensitive as a semantic category to the discrimination of healthy and pathological aging in Spanish language. However, Spanish is significantly more enriched in semantically empty compensatory units (the so-called discourse markers) in comparison with other languages (Ochoa-Obeso, Ivanova, and García Meilán, 2023 (forthcoming); Ivanova, Martínez-Nicolás, and García Meilán 2023).…”
Section: How Does Cross-linguistic Variation Affect Aging Language?mentioning
confidence: 94%
“…Frente al modelo retrogenético, que resultan especialmente interesante para explicar algunos de los fenómenos de cambio en la función lingüística a lo largo de la vida (cf. Ivanova et al, 2020), la disociación categorial parece seguir el modelo lineal que define la organización de las clases léxicas en términos discretos con interconexión gramatical-semántica. xxviii…”
Section: Nombres Y Verbos En El Envejecimientounclassified